REFORMASI PAKTA UNI EROPA TERKAIT KEBIJAKAN MIGRASI DAN SUAKA DALAM UPAYA MENGATASI PENYELUNDUPAN MIGRAN - Sitompul, Imanda Krismayanti (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
This research aims to analyze the EU Migration and Asylum Pact Reform 2024 to address the increasing challenges of migration and human smuggling. The phenomenon of global migration triggered by armed conflict, climate change, and economic inequality has encouraged the European Union to formulate more effective and sustainable migration policies. This research uses a qualitative method with a constructivist paradigm that focuses on how migration policies are shaped through social and political interactions between the actors involved. The results show that although the reform aims to create a fairer and more efficient migration system, implementation challenges remain significant. Political tensions between member states are a major obstacle, especially regarding differing views on refugee quota obligations. In addition, the readiness of the administrative infrastructure in some member states remains an obstacle to implementing this policy effectively. It can be concluded that the EU Migration and Asylum Pact Reform 2024 is a significant step towards a more structured and solidarity-based migration system. However, the EU's inability to reach a full consensus on the implementation of these reforms, mainly due to the opposition of some member states such as Poland and Hungary to migrant redistribution mechanisms, has the potential to undermine the principle of solidarity at the core of these policies. A strict migration policy could exacerbate the EU's internal fragmentation if these political differences are not resolved. Keywords: Reform, Migration and Asylum Pact, European Union, Illegal migration, Human trafficking.